Dampak Perubahan Harga Subsidi (BBM) terhadap Pendapatan Nelayan (Studi Kasus: Dusun Kapuran, Kota Agung, Tanggamus) - Alvina Veronica; Moneyzar Usman (Departement of Mathematics Education, 2023)
This research aims to analyze the effect of changes in subsidized fuel oil (BBM) prices on fishermen's income. Changes in subsidized fuel prices have a significant impact on fishermen's income, because fuel is one of the main components in fishermen's daily activities to earn a living. The research method used in this research uses a descriptive method with a qualitative approach. The data analysis method in this research uses different test analysis with the Paired Simple Test. The results of the research show that there is a significant influence between changes in subsidized fuel prices on fishermen's income. The results of the analysis show that changes in subsidized fuel prices have a significant impact on fishermen's income, because subsidized fuel prices greatly influence the final operating costs of the ship and the fuel costs for traveling around fishing.